Meltdown a free-market look at why the stock market collapsed, the economy tanked, and government bailouts will make things worse - Woods, Thomas E. (Regnery Pub. distributed to the trade by Perseus Distribution, 2009)
Historian Woods, writing as a libertarian, argues that government intervention in the economy actually caused the housing bubble.